PERENCANAAN PENGEMBANGAN KAWASAN JAGUNG SEBAGAI BAHAN BAKU INDUSTRI PAKAN DI KABUPATEN CIAMIS - Mustika Gusnia Sari; Khursatul Munibah; Untung Sudadi (Graduate School Bogor Agricultural University (SPs IPB), 2015)
Poultry development sector in Ciamis has effected an increasing in maize production as a raw material for feed. In period 2008-2012, the production of maize in Ciamis Region is 45.883 tons, meanwhile, the demand is 17.000 tons, consequently the Ciamis District supposed to be able to fulfill the demand; however, but currently the feed industry in Ciamis are still importing the maize. Cluster development might be one of solution for this problem. The aims of this research are: (1) Analyzing land availability for maize development in Ciamis District, (2) Analyzing maize cluster type can be developed in Ciamis District, 3) Analyzing strategies in development of maize cluster. The results showed that land availability for maize development in Ciamis Regency is 28.176 ha. There are three maize cluster types that can be developed in Ciamis as follows: pertumbuhan cluster (15.671 ha), pengembangan cluster (12.217 ha) and pemantapan cluster (288 ha). Considering the region development strategy, the priority in pertumbuhan cluster type is an optimization of natural resources (land factor), in development type is human resources development with focused to the education and training of field staff, and in the pemantapan type is an institution empowerment with focused on the partnerships. Keywords: maize, cluster, development